Analisis Kesesuaian Desain Rumah Tinggal Orang Minangkabau Perantauan terhadap Konsep Greenship Home - Resky Annisa Damayanti; Elda Franzia Jasjfi; Erlina Novianti (Syntax Corporation Indonesia, 2024)
Currently, there are still many who build housing without thinking about the green concept. This causes the problem of global warming. With the very fast development process, especially in Jakarta, it will have an impact on environmental damage. The way to solve this problem is to implement the greenship home concept to residential. The greenship home concept is a development of sustainable development goals (SDG's). The homes of overseas Minangkabau people are said to carry the concept of social sustainability, which is a link between the design of the physical world and the social world, which means that even the comfortable housing is important, home design that is able to maintain social relations and cultural development must also be considered. The culture and traditions of the Minangkabau people who have migrated are still preserved for the sake of continued social interaction or what is known as social sustainability. This research aims to analyze and validate the suitability of residential designs for overseas Minangkabau people, especially those living in Jakarta, to the greenship home concept. The method used is mix-method/combined research which combines qualitative and quantitative approaches. Qualitative with a cultural approach to describe and compare with the standard greenship home assessment system, while quantitative because the data is in the form of numbers. Data was collected through observation and interview methods. The findings of this research are related to the level of suitability of the design of spatial arrangements in the homes of overseas Minangkabau people to the greenship home concept, especially in upper middle class housing in Jakarta, which is in accordance with a percentage of suitability value of 73%, or equivalent to the minimum value at platinum rank (the highest rank ) namely with a score of 56. This research is also expected to become a basis for criticism and evaluation for developers when designing housing in the future.